Kegiatan Deteksi Dini Pemeriksaan Komposisi Tubuh pada Populasi Usia Produktif - Ruslim, Daniel; Destra, Edwin; Gunaidi, Farell Christian; Yulishaputra, Muhammad Daffa Alghifari (Jurnal Suara Pengabdian 45, 2024)
Body composition refers to the distribution of fat, muscle, bone, and other tissues in the human body, which is often expressed as a percentage of total body weight consisting of fat mass and lean body mass. Obesity, characterized by excess fat in adipose tissue, poses a significant health risk and is increasing in countries with low and medium mortality rates, especially in metropolitan areas. Factors contributing to this include genetics, a lack of physical activity, socioeconomic status, unhealthy eating patterns, psychosocial factors, smoking, and alcohol consumption. Excess body fat significantly contributes to morbidity and mortality. Although optimal body fat levels vary, excess fat increases the risk of health issues such as joint problems and cardiovascular disease. People widely use bioimpedance analysis (BIA), an efficient, non-invasive method, to assess nutritional status and body composition. This activity uses the PDCA (Plan-Do-Check-Action) method, which is carried out at PT. Narindo, North Jakarta, in the productive age population. The examination results showed that the average levels of total body fat, visceral fat, total subcutaneous fat, total muscle mass were 28.6%; 11%; 22.2%; 28.3%. Early detection of body composition is critical for assessing nutritional and health status as well as diagnosing disease, potentially reducing obesity-related morbidity and mortality.